2021
DOI: 10.1371/journal.pone.0259125
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential role of copper and cobalt in stimulating angiogenesis for tissue regeneration

Abstract: The use of copper (Cu2+) and cobalt (Co2+) has been described to stimulate blood vessel formation, a key process for the success of tissue regeneration. However, understanding how different concentrations of these ions affect cellular response is important to design scaffolds for their delivery to better fine tune the angiogenic response. On the one hand, gene expression analysis and the assessment of tubular formation structures with human umbilical vein endothelial cells (HUVEC) revealed that high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Indeed, the integration of CoCl 2 in the biomaterials increased angiogenesis. The results corroborated with the previously mentioned findings and further studies [ 105 , 106 ]. Through the use of similar experimental techniques using HUVECs and the in vitro angiogenesis assay, the researchers found enhanced VEGF-A and HIF1-α gene expression in addition to advanced tubal formation in the cobalt treated groups [ 104 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the integration of CoCl 2 in the biomaterials increased angiogenesis. The results corroborated with the previously mentioned findings and further studies [ 105 , 106 ]. Through the use of similar experimental techniques using HUVECs and the in vitro angiogenesis assay, the researchers found enhanced VEGF-A and HIF1-α gene expression in addition to advanced tubal formation in the cobalt treated groups [ 104 ].…”
Section: Discussionsupporting
confidence: 93%
“…Copper and zinc ions have proved their potential as antibacterial, angiogenic and osteogenic components of biomedical materials. In addition to antibacterial properties, copper is one of the most important metals for the human body, since it is involved in several physiological functions, from increasing the expression levels of pro-angiogenic and growth factors (VEGF or FGF-2) to regulating bone metabolism and turnover [ 40 , 41 ]. Zinc is an essential trace element which is needed for immune system functioning and bone development and plays a vital role in the wound healing process [ 13 , 14 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cu 2+ and Co 2+ can promote angiogenesis by contributing to a hypoxic microenvironment and increasing the expression of HIF-α . 109–113 More impressively, Bosch-Rué et al 226 demonstrated that Co 2+ significantly improved the capacity of HUVECs to form tubular structures. Although Fe 3+ still has strong pro-angiogenic effects, 227 its relatively high cytotoxicity and the oxidative damage it causes limit its further application.…”
Section: Regulating Bone Metabolism With Metal Ionsmentioning
confidence: 99%